Rethinking Consumer Protection Policy in Financial Markets - Haim, Liran (Journal of Law and Commerce, 2013)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US JA HE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> <!–StartFragment–> Financial products for consumers usually are characterized by complexity and incomprehensibility. Consumers typically find themselves defeated when attempting to control their financial destiny by understanding these products. This Article explores the economic and social factors that lead to this reality, analyzes its highly negative private and social ramifications and proposes an appropriate policy response. I argue that the current market structure creates a reality in which financial institutions are motivated to produce complex financial products for consumers in order to maximize their profits. This market structure, combined with inadequate policy, induces inefficiency by allocating the comprehension costs of financial products to the consumer. My thesis is that a fundamental change in risk allocation policy will steer the market toward consumer comprehension of financial products and, therefore, will reduce private and social costs, increase consumer trust in financial institutions and promote social cohesion. I propose a new default liability rule under which financial institutions would be required to introduce internal procedures and mechanisms to ensure product comprehension among all of their consumers. To encourage maximum compliance with my proposal, I suggest implementing a reputation-based incentives method that would require every financial institution branch to publicly post a service quality ranking assigned by the regulator. I also support a trust-oriented licensing policy that would encourage the inclusion of new trustworthy financial institutions in the market and offer the implementation of a new regime for supervising financial product contract terms. <!–EndFragment–>